Non-wet kingfisher flying in the rain: the tumble of droplets on moving oriented anisotropic superhydrophobic substrates - Zheng, Yihua; Zhang, Chengchun; Wang, Jing; Yang, Liang; Shen, Chun; Han, Zhiwu; Liu, Yan (American Chemical Society, 2020)
Extensive studies of antiwetting have been restricted to stationary substrates, while dewetting mechanisms on moving interfaces are still poorly understood. Due to the hydrophobic and anisotropic surface characteristics of kingfishers, they are able to easily change flight direction even under high-intensity precipitation. The present study aims to mechanistically analyze how the synergy of interfacial movement, anisotropy, and superhydrophobicity affects rapid dehydration. We have designed a droplet-conveyor system to simulate the bouncing of droplets on moving anisotropic superhydrophobic targets and performed simulations via the lattice Boltzmann algorithm. The moving interface can induce a directional tumbling behavior of the droplet and effectively avoid continuous wetting in the same region. We found that droplet tumbling is essentially caused by transformed depinning velocity vectors at the interface downstream. Also, the hang time of a tumbling droplet is positively related to the angle between the motion vector and the texture. The oriented anisotropic motion facilitates the tumbling of droplets and decreases their hang time by up to 23% as compared to that on a stationary inclined superhydrophobic surface. Similar interfacial process dehydration also occurs on a nonwet kingfisher flying in the rain, and we believe that these findings provide valuable new insights for high-efficiency water repellency of surfaces
Keywords: kingfisher; depinning; superhydrophobic anisotropy; rapid dewetting; droplet conveyer